Kepemimpinan dalam Agama Hindu Studi Naskah Lontar Nitipraya - Aris Hidayat (Balai Penelitian dan Pengembangan Agama Semarang, 2009)
In Bali, it has been a long tradition to write on such palm leaves. Several of thosemanuscripts contained leadership stories. This reseach utilized content analyzesapproach and Roland Barthe's semiotics post structural method. Leadership thoughtsin Nytipraya manuscript called siksakarya described through the nature and behaviorsof crow and rooster. This manuscript is full of very good moral lessons for leaders. Inadditional to moral lessons contained in siksakarya, there is also Pancaksara lesson.This thought guided someone in order to free from dissasters and suffers coming fromall directions. To achieve this goals, someone has to follow self-approach stages to theGod (Sang Hyang Widhi) including tapa, brata, yoga and meditation stages. All aredirected to basic human goals as in Hinduism concepts of dharma, artha, kama andmoksa.Key Words: Palmyra Palm, Leadership, Siksakarya, Pancaksara